Rapid Expansion of a Large Oral Pyogenic Granuloma in a Pediatric Patient: A Case Report - Felipe Mesquita Araújo; Maria Gabriella Luzia de Oliveira Martins; Reuber Mendes Rocha; Satiro Watanabe; Patricia Corrêa‐Faria; Fernanda Paula Yamamoto‐Silva; Brunno Santos de Freitas Silva (International Journal of Paediatric Dentistry, 2026)
Why This Paper Is Important to Pediatric Dentists The rapid growth and clinical appearance of pyogenic granuloma (PG) may mimic malignant neoplasms, requiring careful clinical evaluation. PG should be considered in the differential diagnosis of rapidly growing oral masses and distinguished from malignant lesions. Histopathological examination is essential for establishing an accurate diagnosis and guiding appropriate management.